“Chile despertó": the political meanings in the October Revolt (Polis (Santiago), 2022)
This article analyzes the Chilean social uprising of October 2019 onwards, based on qualitative research carried out in three regions of the country: Santiago, Valparaíso, and Concepción. It is suggested that, although this can be considered as a culminating event in the mobilization cycle that began in 2006 in the country, it presents elements that make it qualitatively different from that process. (a) Protests took the form of a social outbreak and, although their demands converged with those expressed in previous mobilizations, they were not led by the organizations that participated in that process. This implied that the massiveness, the repertoires of protest, the diffusion, and the forms of convocation of the outbreak reached people who had not previously demonstrated in the street and who were not linked to parties or social organizations. (b) Secondly, it is proposed that the political senses generated from the protests allow us to understand, to a large extent, the electoral success of independents in the election of constituents, in October 2020.
Keywords: Social outbreak; first time-protesters; contentious politics; Constitutional Convention